Предмет: Алгебра,
автор: msdedushko
(a+3b) 1 b
( --------- – --- ) : --------
a(a-3b) a 3b - 1
Ответы
Автор ответа:
0
при делении дробь переворачиваем и будет умножение
((a+3b)/a(a-3b))-1/a)*(3b-1)/b
=(a+3b-(a-3b))/a(a-3b))*
(3b-1)/b=(6b*(3b-1))/ab(a-3b)
=(6(3b-1))/a(a-3b)
((a+3b)/a(a-3b))-1/a)*(3b-1)/b
=(a+3b-(a-3b))/a(a-3b))*
(3b-1)/b=(6b*(3b-1))/ab(a-3b)
=(6(3b-1))/a(a-3b)
Похожие вопросы
Предмет: География,
автор: frez044
Предмет: Геометрия,
автор: fatimamestanova3
Предмет: Русский язык,
автор: Tupoylosos02
Предмет: Химия,
автор: Манзырыкчы
Предмет: Математика,
автор: fabilondon